INTEGRASI ILMU KEISLAMAN MI DALAM PEMBENTUKAN KARAKTER GENERASI EMAS - Shindy Lestari; Khamim Zarkasih Putro (Jurnal Pendidikan Islam, 2021)
adrasas as educational institutions that equip students by integrating sciences such as natural, social, and exact sciences based on religious knowledge so that students are able to follow the development of science and technology. This research aims as a study material and provides information and solutions to efforts that can be applied to the integration of Islamic Madrasah Ibtidaiyah in character building in the golden generation. This research uses a qualitative type of descriptive-analytical approach with a literature review model. This research data collection technique looks for data about things or variables in the form of notes, documents, papers, articles and journals. The results showed that madrasah ibtidaiyah is an Islamic basic education institution that combines Islamic boarding school and school education by integrating religion and general knowledge, but perfects each other without having to eliminate the uniqueness between the two sciences, so that they can meet National education by creating a generation of character, knowledge and skills.